IDENTIFIKASI MANGIFERIN DAN UJI AKTIVITAS PENGKELAT BESI PADA EKSTRAK DAUN MANGGA (Mangifera indica L.) : IDENTIFIKASI MANGIFERIN - KRISTYANTI, YULIA; Lutsina, Novi Winda; More, Evanisia (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2023)
Blood disorder caused by unbalanced globin synthesis resulting in damage to hemoglobin and recessive inheritance, handling do regular blood transfusions. Repeated blood transfusions in the long term lead to the accumulation of iron in the body. The purpose of this study was to determine the content and of mangiferin activity extract M. indica L leaf as an iron chelating in vitro. indica L leaf extract obtained by maceration method with 96% ethanol. Testing mangiferin content by TLC methods and iron chelating effectiveness in vitro using methods Ferrous ion chelating (FIC), the principle of the method is to measure the ability of a compound to compete with ferozine the metal chelate iron. Identification of TLC revealed that there is content mangiferin on leaf extract M indica L, by the similarity of color patches and Rf extracts and mangiferin, by using three types of the mobile phase is n-hexane: ethyl acetate: water (6: 3: 1) with Rf 0.1, ethyl acetate: formic acid: water (8: 2: 1) with Rf of 0.34 and methanol: chloroform: water (7: 2: 1) with Rf 0.8, Test result the ability of the metal chelate extract M. indica L leaf of ethanol has an iron chelating effect as in vitro methods FIC. Concentration higher of the iron chelating higher percentage. Extract at concentrations of 1, 10, 20, 30 and 40 ug / ml respectively have iron chelating percentage 6,44%, 29,87%, 58,85%, 75,74% and 92,99%, with values (IC50) it is 18,73 µg/ml.